Control of Apoptosis in Treatment and Biology of Pancreatic Cancer. Issue 2 (February 2016) - Modi, Shrey; Kir, Devika; Banerjee, Sulagna; Saluja, Ashok
ABSTRACT: Pancreatic cancer is estimated to be the 12th most common cancer in the United States in 2014 and yet this malignancy is the fourth leading cause of cancer‐related death in the United States. Late detection and resistance to therapy are the major causes for its dismal prognosis. Apoptosis is an actively orchestrated cell death mechanism that serves to maintain tissue homoeostasis. Cancer develops from normal cells by accruing significant changes through one or more mechanisms, leading to DNA damage and mutations, which in a normal cell would induce this programmed cell death pathway. As a result, evasion of apoptosis is one of the hallmarks of cancer cells. PDAC is notoriously resistant to apoptosis, thereby explaining its aggressive nature and resistance to conventional treatment modalities. The current review is focus on understanding different intrinsic and extrinsic pathways in pancreatic cancer that may affect apoptosis in this disease. J. Cell. Biochem. 117: 279–288, 2016. © 2015 Wiley Periodicals, Inc.